Effect of Er,Cr:YSGG Laser and Remin Pro on Microhardness of Enamel White Spot Lesions Induced by Orthodontic Treatment: Effect of Er,Cr:YSGG Laser and Remin Pro on Microhardness - Toodehzaeim, Mohammad Hossein; validad, Hanieh; Rafiei, Elahe; Haerian, Alireza; Molla, Reza; Safaei, Mohammad (Regeneration, Reconstruction & Restoration (Triple R), 2025)
Background and objectives: White spot lesions (WSLs) are one of problems caused by orthodontics treatment, resulting from enamel demineralization and leading to compromised esthetics and mechanical integrity. Recently, sub-ablative erbium laser irradiation and remineralizing agents like Remin Pro toothpaste (a hydroxyapatite-based remineralizing agent) have been proposed as potential approaches to enhance enamel resistance to demineralization. This in vitro study aimed to evaluate the effect of Er,Cr:YSGG laser irradiation and Remin Pro toothpaste on the microhardness of enamel white spot lesions following orthodontic treatment. Materials and methods: Fifty sound extracted premolars were selected, and artificial white spot lesions were created using a standardized demineralization protocol. The samples were randomly allocated into experimental groups, including Er,Cr:YSGG laser irradiation, Remin Pro application, and a combination of both interventions. Laser irradiation was performed under sub-ablative conditions using an Er,Cr:YSGG laser (wavelength: 2780 nm) with predefined parameters for power, pulse mode, energy density, and water cooling. Enamel microhardness was assessed at different depths using a Vickers microhardness tester. Data were analyzed using SPSS (version 23) via two-way ANOVA and Tukey’s tests at a 0.05 significance level. Results: Statistically significant differences in enamel microhardness were observed among the experimental groups as well as across different enamel depths (P < 0.05), with the highest microhardness values recorded in the combined laser and Remin Pro group in 150 micrometers depth. Conclusions: Within the limitations of this in vitro study, Er,Cr:YSGG laser irradiation, particularly when combined with Remin Pro toothpaste, may enhance the mechanical integrity of enamel white spot lesions and improve their resistance to demineralization.